2015
DOI: 10.21273/hortsci.50.5.666
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Acquired Resistance Induced by Agrobacterium tumefaciens in Peach and Differential Expression of PR1 Genes

Abstract: Crown gall disease caused by Agrobacterium tumefaciens affects a wide range of horticultural plants, and has no effective treatment. During the evaluation of crown gall resistance of peach germplasm resources, we observed enhanced resistance to subsequent invasion that was activated by virulence of A. tumefaciens in two peach cultivars. To further verify the phenotype observed in field experiments, systemic acquired resistance (SAR)-related salicyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The efficient inhibition of A. tumefaciens by "protective" endophytes might maintain the pathogen population below the threshold required for quorum sensing, restrict the T-DNA transfer from A. tumefaciens to peach, and cause smaller galls (60). Furthermore, it has been reported that salicylic acid (SA)-induced systemic acquired resistance is activated in "Honggengansutao" by pathogen infection (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficient inhibition of A. tumefaciens by "protective" endophytes might maintain the pathogen population below the threshold required for quorum sensing, restrict the T-DNA transfer from A. tumefaciens to peach, and cause smaller galls (60). Furthermore, it has been reported that salicylic acid (SA)-induced systemic acquired resistance is activated in "Honggengansutao" by pathogen infection (9).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 180 peach plants were grown in the greenhouse experiment (90 per cultivar), including 45 plants of each cultivar inoculated with A. tumefaciens on root collars (I) and 45 mock-inoculated plants used as controls (M). The pathogen inoculation was performed as described by Hao et al (9). Cuts of 1 cm in length were made into the cambium at the root collar, and 20 l of either bacterial inoculum (10 9 CFU/ml) or sterile deionized water was applied to the incision, which was then covered by autoclaved vermiculite.…”
Section: Methodsmentioning
confidence: 99%
“…Although no genes for resistance to crown gall have been described, differences in tolerance against A. tumefaciens have been observed in different Prunus species . In a recent work, Hao et al . observed two peach cultivars with enhanced resistance to A. tumefaciens .…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial cells provoked expression of plant defense genes including PAL, POD, and CrPR1a genes with a lag period of 12-24 h. In agreement with these results, Ditt et al (2001) observed differential expression of defense genes in Ageratum conyzoides cell culture bout 24 h post-infection with A tumefaciens. A longer lag period of 3 days was observed by Hao et al (2015) for PR-1 genes in peach plants. The same lag period was recorded for PR-10 and POD genes in grape embryonic callus (F. Zhao et al, 2011).…”
Section: Discussionmentioning
confidence: 87%